Building resilience among rural and remote nurses in Queensland, Australia. Issue 3 (June 2020) - Terry, Victoria R.; Graham, Coralie J.; Rogers, Cath; Craigie, Mark; Hegney, Desley G.; Rees, Clare S.; Small, Chris
Abstract: Aim: This study evaluated a workplace resilience intervention involving registered nurses working in rural and remote settings in Queensland, Australia. Background: The nature of nursing work provides a range of challenges to the psychological well-being of nurses. To address these challenges, research in the area of building resilience to enhance psychological well-being among nurses is growing rapidly, although few studies have investigated these phenomena in rural and remote settings. Design/methods: The study implemented and evaluated a Mindfulness Self-Care and Resiliency (MSCR) program delivered to registered nurses ( N  = 32) working in rural or remote locations, to enhance workplace resilience. Registered nurses who attended the program were invited to evaluate the program via a semi-structured telephone interview. Results/findings: Qualitative analysis showed that most nurses found the MSCR program valuable and relevant in terms of learning new knowledge and skills to help build resilience to stress in the workplace. Conclusion: The MSCR intervention was received positively by the registered nurses who participated and may have broader application across the rural healthcare sector.